The 'ivory tower' as safe bet: Science policies and research evaluation in Mexico - Federico Vasen (Arizona State University, 2018)
The article analyzes the signals received by social researchers in Mexico regarding the type of production expected from them in merit pay programs. The institutional public discourse embodied in official documents is contrasted with the description of the evaluation carried out by the evaluators themselves. The research is based in document analysis and semi-structured interviews to evaluators. The main conclusion of the study is that there is an asymmetry between the public discourse of the institutions and the behaviors that are rewarded in the evaluation practices themselves. While the political discourse  promotes a model of researcher committed to knowledge transfer and mobilization activities , academic evaluation practices encourage a classic academic profile. These contradictions could be explained by the ability of scientists to influence the content of policies in pursuit of their own interests. On the other hand, from the point of view of policymakers, the weight that international publications have for university rankings could exempt scientists from giving another justification for the importance of their work.